Analysis of the Role of Tourism Aware Groups in Developing the Potential of Olean Village During Pandemic - Anies Firdyanti Kusuma; Maria Ulfa Nur Rahmatillah; Isti Fadah (UPT Penerbitan Universitas Jember, 2021)
The purpose of this study was to determine the extent of the role of tourism awareness groups in developing the potential of Olean Village during the pandemic. Olean Village has three tours at once, namely, educational tours, cultural tours, and historical tours. The potential of Olean Village tourism is currently not managed optimally and still relies on correct management techniques so that it has not shown significant development. This study seeks to find a solution to this phenomenon, researchers conduct data mining using SWOT analysis to find out important operational aspects in the form of strengths, weaknesses, opportunities, and threats. The next analysis is to examine developments that can be done to attract people's interest to visit tourism in Olean Village, especially during the pandemic. The results of the analysis show that it is necessary to develop innovation by making organizational structures and promotion systems that utilize digital media. The results of this study can be a solution in the form of tourism development recommendations by utilizing the role of tourism awareness groups in Olean Village while still involving internal parties, namely the Olean Village community and also external parties, namely support from the Situbondo Regency Government. Keywords: POKDARWIS, Olean Village, Tourism